2022
DOI: 10.1093/brain/awac104
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of serum prolactin links the hypothalamus with female nociceptors to promote migraine

Abstract: Migraine headache results from activation of meningeal nociceptors, however, the hypothalamus is activated many hours before the emergence of pain. How hypothalamic neural mechanisms may influence trigeminal nociceptor function remains unknown. Stress is a common migraine trigger that engages hypothalamic dynorphin/kappa opioid receptor (KOR) signaling and increases circulating prolactin. Prolactin acts at both long and short prolactin receptor isoforms (PRLR-L and PRLR-S) that are expressed in trigeminal affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 101 publications
3
35
0
Order By: Relevance
“…In a recent study, Watanabe and colleagues revealed that stressinduced activation of hypothalamic kappa opioid receptor increased circulating PRL, resulting in increased sensitization of trigeminal nociceptors, which thereby promote migraine pain from normally innocuous stimuli. 37 Altogether, these findings implicate PRL and PRLR, particularly PRLR-S, in signaling pathways underlying migraine. Whether PRL administration or direct modulation of PRL signaling cause migraine…”
Section: Discussionmentioning
confidence: 93%
“…In a recent study, Watanabe and colleagues revealed that stressinduced activation of hypothalamic kappa opioid receptor increased circulating PRL, resulting in increased sensitization of trigeminal nociceptors, which thereby promote migraine pain from normally innocuous stimuli. 37 Altogether, these findings implicate PRL and PRLR, particularly PRLR-S, in signaling pathways underlying migraine. Whether PRL administration or direct modulation of PRL signaling cause migraine…”
Section: Discussionmentioning
confidence: 93%
“…Recently, it was shown that PRL could be targeted more upstream as well, using kappa opioid receptor (KOR) antagonists. Stress-activated hypothalamic KORs were shown to increase PRL levels resulting in trigeminal sensitization, with effects in both male and female mice, suggesting that these KOR antagonists could potentially be used for migraine prophylaxis in both sexes, while decreasing PRL levels using the dopamine receptor agonist, cabergoline, seemed to be effective for reducing allodynia in only females, without any effect on males [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study found lower nocturnal PRL peaks in patients with CM compared to healthy controls [ 123 ]. Thus, elevated PRL levels may potentially worsen migraine symptoms or lead to migraine chronification [ 106 , 124 , 125 ].…”
Section: Prolactin Levels In Migraine Patientsmentioning
confidence: 99%
“…The diencephalon may be, indeed, strongly involved in the process of allodynia. Stress-related hypothalamic dysregulation of prolactin has recently been associated with allodynia in females [ 256 ]. Activation in posterior thalamic areas was demonstrated in rodents and also in migraine patients with extracephalic allodynia, with functional MRI BOLD techniques [ 257 ].…”
Section: Neuro-otological Manifestationsmentioning
confidence: 99%